A study of the ideal model of the sports pharmacist in Japan's top sports - Otsuka, S.; Seino, J.; Oshiba, Y.; Ogata, M. (Japan Journal of Physical Education, Health and Sport Sciences, 2023)
The purpose of this study was to clarify the roles required of sports pharmacists (SPs) from various perspectives related to anti-doping (hereinafter referred to as "AD") in Japan`s top sports. The subjects of the survey were "those engaged in AD activities as SPs" (2 SPs active in central sports organizations), "those familiar with SPs and AD activities and promoting them" (1 managing director of the Japan Anti-Doping Agency), and "those receiving support from SPs regarding AD" (1 person in charge of strengthening of a central athletic organization and 2 Olympic medalists), who are involved in Japan`s top sports. The subjects were asked to participate in semi-structured interviews, and the data obtained were analyzed using a modified grounded theory approach. The results revealed that: 1) As experts who can be consulted about concerns related to medication and supplement use, the subjects provide information and AD education; 2) As medication and AD experts who protect the health of athletes, the subjects collaborate with physicians and make efforts to further improve their own qualifications and abilities; 3) As familiar support staff recognized in the community and society, the subjects are proactive in providing information and AD education; and 4) As experts who can be consulted about concerns regarding medication and supplement use, the subjects provide information and AD education, thus making an active contribution to society at large as familiar support staff recognized in the community and society. In conclusion, this study has shown that SPs support the safe use of drugs by athletes in Japan through their expertise, thus contributing to not only the field of AD but also the protection of health. They are recognized by the community and society as drug specialists who contribute to sports, and have become a familiar presence for athletes.